Siemens Industry Software Pte Ltd v Lion Global Offshore Pte Ltd [2014] SGHC 251: Further Issues in Contractual Formation and Duress - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2014)
For a second time in a month, the High Court decision of Siemens Industry Software Pte Ltd v Lion Global Offshore Pte Ltd [2014] SGHC 251 (“Siemens Industry Software”) gives us valuable guidance on the application of trite principles of contractual formation to a practical fact pattern. The case also discussed whether enforcing one’s legal right can ever amount to duress.